Distribution, Habitat, and Productivity of Tundra Swans on Victoria Island, King William Island, and Southwestern Boothia Peninsula, N.W.T. - Stewart, D. Bruce; Bernier, Lionel M.J. (ARCTIC, 1989)
Data on tundra swans (Cygnus columbianus columbianus) were recorded in the central and eastern Canadian Arctic, south of 77 N latitude, and on Southampton Island during the summers of 1980-85. Swans were seen on Victoria, Royal Geographical Society, King William, Stanley, and Southampton islands and on southwestern Melville and Boothia peninsulas. Most swans inhabited low-lying areas that were inundated by the sea following glaciation and are now dotted with shallow tundra ponds. Breeding swans were common in the Minto Inlet, Lady Franklin Point, and Cambridge Bay areas of Victoria Island and on King William Island and southwestern Boothia Peninsula. In August, 52-89% of the adults and subadults in these areas were seen as potential breeders, and the remainder were in nonbreeding flocks. Between 17 and 33% of the pairs had cygnets, and 10-13% of all swans were cygnets. With brood sizes of 1-3 (1.5 ±0.7 [mean ±SD] to 1.6 ±0.5), the apparent breeding success was low relative to other northern swan populations. However, these breeding populations are significant and should be considered in management plans for the eastern population of the tundra swan.Key words: arctic birds, Canada, Cygnus columbianus columbianus, distribution, habitat, Northwest Territories, productivity Mots clés: oiseaux arctiques, Canada, Cygnus columbianus columbianus, distribution, habitat, Territoires du Nord-Ouest, productivité